Ўйин орқали болалар монологик нутқини шакллантириш йўллари - Джолымбетова, М.М; Гулмуратова, К (SCIENCE and SOCIETY, 2023)
The problem of speech development of children of preschool agerast, speech defects and the formation of monologue
Keywords: children's age; speech; monologue speech; game activity; treatment program; pedagogical and psychological technology